Synthesis, Characterization and Luminescent Properties of Green Phosphor BaMoO4:Tb3+ - Zhang, Jianfu; Zhu, Lili; Xie, Jianping; Chen, Yuanpeng; Wang, Zhenling (Asian Journal of Chemistry, 2015)
The green phosphor BaMoO4:Tb3+ was prepared by sol-gel method. The effects of doping concentration and sintering temperature on the crystal structure and luminescent properties were investigated by X-ray powder diffraction, scanning electron microscope, UV-visible spectroscopy and photoluminescence spectroscopy. The XRD results showed a pure BaMoO4 phase can be obtained when calcinating phosphor at 900 °C. The photoluminescence spectroscopy spectra exhibited four peaks, the most intense peak of 542 nm can be attributed to 5D4 ® 7F5 transition of Tb3+ and the optimized mol percent of Tb3+ was 0.05. All the results indicated that BaMoO4: Tb3+ could be used as a white-light emitting diodes ultraviolet photoexcitation green phosphors.